Sanskrit educational texts in Kawi culture; The case of the "Kārakasaṁgraha" - Aminullah, Zakariya Pamuji; Rahayu, Yosephin Apriastuti (Wacana, Journal of the Humanities of Indonesia, 2025)
This article provides a revised critical edition and annotated translation of the Kārakasaṁgraha, a Sanskrit grammatical treatise as it has been preserved in Balinese manuscripts. The work is a synthesis of Indian grammatical traditions, notably including aspects of both Pāṇinian and Kātantra systems, which was probably recomposed in the premodern Indonesian archipelago. While its Sanskrit matrix is witness to local adaptation, the interspersed Old Javanese commentaries also show a striking reframing of grammatical discourse in ritual and cosmological idioms. Rather than merely clarifying rules of language, the glosses link grammatical analysis to devotional practice and calendrical systems, presaging a broader epistemological transformation. The study argues that the Kārakasaṁgraha was not just a pedagogical text but also a ritual-linguistic manual, blurring the lines between grammar, spirituality, and cosmology. This dual concern offers new insights into the vernacularization of Sanskrit in Southeast Asia and demonstrates the creative intellectual gestures of Old Javanese intellectuals in sacralizing linguistic knowledge.